Birth weight interacts with a functional variant of the oxytocin receptor gene (OXTR) to predict executive functioning in children. (17th May 2017) - Wade, Mark; Prime, Heather; Hoffmann, Thomas J.; Schmidt, Louis A.; O'Connor, Thomas G.; Jenkins, Jennifer M.
Abstract: Genetic variation in the oxytocin receptor gene ( OXTR ) is associated with several psychiatric conditions characterized by deficits in executive functioning (EF). A specific OXTR variant, rs2254298, has previously been associated with brain functioning in regions implicated in EF. Moreover, birth weight variation across the entire range is associated with individual differences in cortical structure and function that underlie EF. This is the first study to examine the main and interactive effect between rs2254298 and birth weight on EF in children. The sample consisted of 310 children from an ongoing longitudinal study. EF was measured at age 4.5 using observational tasks indexing working memory, cognitive flexibility, and inhibitory control. A family-based design that controlled for population admixture, stratification, and nongenomic confounds was employed. A significant genetic association between rs2254298 and EF was observed, with more copies of the major allele (G) associated with higher EF. There was also a significant interaction between rs2254298 and birth weight, such that more copies of the major allele in combination with higher birth weight predicted better EF. Findings suggest that OXTR may be associated with discrete neurocognitive abilities in childhood, and these effects may be modulated by intrauterine conditions related to fetal growth and development.